Impact of Quetiapine Therapy on QTc Prolongation in Critically Ill Patients. Issue 7 (July 2019) - Lee, Sue; Morris, Amanda; Kim, Sarah; Li, Fanny; Baumgartner, Laura
Background: Quetiapine is an atypical antipsychotic commonly utilized for the management of delirium in critically ill patients. The impact of quetiapine on QTc in the critically ill population is largely unknown.Objective: The purpose of this study was to evaluate QTc prolongation following administration of quetiapine for the management of delirium in critically ill patients.Methods: This was a single-center prospective, observational cohort study. QTc measurements of patients who received at least one dose of quetiapine were compared with a control group receiving melatonin. The primary outcome was mean change in QTc from baseline to maximum serum drug concentration after the first dose of quetiapine.Results: No significant change in QTc was observed from baseline to post–quetiapine administration, with a mean change in QTc of 2.7 ms (438.4 ± 43.2 ms vs 441.1 ± 36.4 ms; P = 0.50). When comparing mean change in QTc between the quetiapine group and melatonin group, the difference was not significant (2.7 ± 37.8 ms vs −0.18 ± 32.0 ms, P = 0.73).Conclusion and Relevance: This study represents one of the first prospective studies evaluating the impact of quetiapine on QTc. The results of this study demonstrate a nonsignificant statistical and clinical change in the QTc following quetiapine administration in critically ill patients utilizing telemetry measurements. Routine QTc monitoring with formal electrocardiogram(s) following quetiapine administration may not be warranted.